Hydrogen peroxide as a preservative of milk - Miyawaki, Atsushi (My University, 1907)
Introduction: Since Prof. Leze wrote in Journal d' Agriculture Practique about hydrogenperoxide as a preservative of milk, the public has been very much aroused. Scientific and dairy papers presented quotations directly or indirectly from his article. Experiments were performed by M. M. de'Waele, Sugg and Vandevelde. In conclusion these gentlemen said "an absolute sterilization is obtained by using hydrogenperoxide in excess and the excess may be neutralized by blood serum previously passed through a Chamberland filter". The objects of the following experiments were to find out whether or not an absolute sterilization cam be obtained from hydrogen peroxide, as above mentioned gentlemen said, to find out what bearing it has on adulteration of milk, and to find out whether this is a practical thing to be used in dairying.
Citation: Miyawaki, Atsushi. Hydrogen peroxide as a preservative of milk. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Hydrogenperoxide; Preservatives in Milk; Experimentation; Food Science; Theses